Investigating Balance Process in Enterpreneur Gamified Scenarios - Tizuka, Michelle M.; Clua, Esteban W. G.; Salgado, Luciana C. C. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais Estendidos do XXI Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2022.226125, 2022)
To non-experts, balancing consciousness is even harder concerning their perception of how their decisions possibly affect employees. In this work, we interviewed three managers to understand their knowledge of balancing and their level of perception of the theme. Our results indicate they know it can affect user satisfaction, but they do not know precisely how. Also, visualization of a balanced progression system is an issue. Therefore, we generated a gamification process model that facilitates communication among project managers. Future work will implement this model and conduct an evaluation study of user satisfaction and perceived balancing based on this gamification balancing approach.